Upaya Peningkatan Pengetahuan Pencegahan Anemia Remaja SMAS Muhammadiyah Kota Ternate - Agustin Rahayu; Diah Merdekawati Surasno; Andiani Andiani; Suryani Mansyur; Mayasari Soamole; Musiana Musiana; Siti Nurhidayanti; Monissa A.Hi. Jafar; Norma Toduho; Tati Sumiati; Tutik Lestari; Rahmania N Wambes; Aswia Arsad; Dessy Tanassi; Della Basri; Kiki Muslim (Jurnal Medika: Medika, 2024)
Anemia is a public health problem that has a negative impact on the cognitive abilities and physical capacity of adolescents. In Indonesia, the prevalence of adolescents aged 15-24 years experiencing anemia is 32% according to 2018 Riskesdas data. The aim of this community service is to increase the knowledge of Muhammadiyah High School students in Ternate City regarding nutrition, especially regarding anemia and its prevention. So you have the awareness to choose nutritious food which can prevent anemia and its negative effects in the future. The community service methods used are counseling and measuring nutritional status (BMI/U) for all students and measuring upper arm circumference (LILA) specifically for female students. Before the counseling was held, a pre-test was held for all students which was then followed by counseling on Preventing Anemia and discussion. Final Evaluation by carrying out a post test. The results obtained showed that there was a significant increase in students' knowledge (p=0.00), namely 2.69 points. The conclusion of community service is that counseling on preventing anemia is very useful for students in increasing their knowledge and awareness in behaving in a nutritionally conscious manner.